2020
DOI: 10.1038/s41598-020-68188-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and anti-oxidant potential on essential oils of Thymus quinquecostatus Celak. from Loess Plateau in China, regulating Nrf2/Keap1 signaling pathway in zebrafish

Abstract: Chemical profile and antioxidant potency of essential oils (EOs) of Thymus quinquecostatus celak. (thyme oils) obtained from Loess Plateau in China had been studied. 130 constituents of thyme oils were determined using gas chromatography-mass spectrometry (GC-MS) and carvacrol ethyl ether was firstly reported as a new natural product, which has been used as a synthetic flavoring substance with no safety concern. The thyme oils showed the anti-oxidant activity using 2,2 diphenyl-1-picrylhydrazyl (DPPH), 2,2′-az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…According to researches research, carvacrol was one of the characteristic components of Thymus plants. Carvacrol was founded in T. quinquecostatus EO from Loess Plateau [15] . However, carvacrol was not found in the EO collected from Yantai, China.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…According to researches research, carvacrol was one of the characteristic components of Thymus plants. Carvacrol was founded in T. quinquecostatus EO from Loess Plateau [15] . However, carvacrol was not found in the EO collected from Yantai, China.…”
Section: Resultsmentioning
confidence: 90%
“…Records of the medicinal use of T. quinquecostatus can be traced back to the Song Dynasty (A. D. 960–1279). At present, T. quinquecostatus is widely used to treat stroke, cold, dyspepsia, toothache, acute gastroenteritis, hypertension, chronic eczema and other diseases as folk medicines and was used alone or in combination with other herbal medicines for cancer treatment [15,16] . T. quinquecostatus has antioxidative effects that can mediate the inflammatory response and prevent cell damage through its antioxidant activities [17] .…”
Section: Introductionmentioning
confidence: 99%
“…By inhibiting lipid peroxidation and activation of the Keap1/Nrf2 pathway in zebrafish, Thymus quinquecostatus Celak. oils have provided protection against oxidative stress in zebrafish, as demonstrated by He et al [81]. TEO treatment effectively restored the antioxidant defense mechanism by increasing the antioxidant levels of activity in the brain.…”
Section: Effects On the Brain Oxidative Statusmentioning
confidence: 90%
“…Additionally, a previous study has shown that Thymol exhibits a lower toxicity (3× higher LC 50 of 42.35 μM~6.36 mg L −1 ) [ 19 ] in comparison to the current study, which could be explained by different species’ sensitivities among different laboratories. Notwithstanding, craniofacial and skeletal deformities were similarly observed at higher concentrations (50 μM~7.5 mg L −1 [ 19 ] and 40 mg L −1 [ 20 ]), further supporting the teratogenic potential of Thymol to zebrafish embryos, even at lower concentrations. During embryogenesis, cells acquire distinct functions and specific positions, giving rise to a functional, complex, and multicellular organism through a set of early molecular and cellular mechanisms [ 41 ].…”
Section: Discussionmentioning
confidence: 72%
“…For instance, horsetail ( Equisetum arvense ) was the first approved basic substance according to the European Regulation (EC) 1107/2009 [ 13 ], but, although not considered as a substance of concern, it has been associated with potential neurodevelopmental toxicity [ 14 ]. Likewise, “jurema preta” ( Mimosa tenuiflora ) has been described as teratogenic to higher vertebrates [ 15 , 16 ], and Thymol, the main monoterpene phenol isolated from plants from the Lamiaceae family such as Thymus vulgaris L. [ 17 ], has been shown to cause developmental abnormalities in chicken and zebrafish embryos [ 18 , 19 , 20 ] and to regulate cholinergic and antioxidant systems in cognitive dysfunctional zebrafish [ 21 ]. However, although current research shows its antifungal properties [ 17 , 22 , 23 ] and some commercial pesticide products based on natural compounds are available on the market, there is a lack of sufficient neurodevelopmental information, and further studies are needed to clarify their environmental risk to non-target organisms to define efficient and appropriate use patterns.…”
Section: Introductionmentioning
confidence: 99%